Perception of Low-Income Communities Toward Yos Sudarso Public Housing in Pekanbaru City - Layla Turrahmi; Ahmad Sarwadi (Eduvest - Journal of Universal Studies, 2024)
The city of Pekanbaru has experienced an uncontrolled increase in population, leading to the creation of slum settlements. The construction of low-cost apartments (rusunawa) has emerged as a potential solution to address the ambiguity in urban planning regarding housing for low-income residents. Pekanbaru has several rusunawa, but only two are specifically designated for low-income residents: Rejosari rusunawa and Yos Sudarso rusunawa. Over five years of operation, Yos Sudarso rusunawa has shown an occupancy rate of less than 50%, indicating the low perception among Pekanbaru's low-income residents about moving to the rusunawa and their preference to remain inadequate housing. This study is deemed necessary to understand the perceptions and factors influencing the perceptions of low-income residents so that the existing rusunawa can function properly. The research employs a descriptive quantitative method. The quantitative method uses statistical tests in SPSS, employing Spearman's rho correlation analysis to examine the relationship between factors and perception, followed by ordinal logistic regression analysis to identify the most influential factors on the perception of living in Yos Sudarso rusunawa. The study on perception of low-income residents towards Yos Sudarso rusunawa in Pekanbaru found that their perception is generally negative. Several factors influence perception of low-income residents towards Yos Sudarso rusunawa, namely economic factors (affordability) and the physical condition of the rusunawa. The physical condition of the rusunawa is the primary factor affecting the perception of low-income residents, with a significant value of 0.005, followed by the affordability of rental prices, which has a significant value of 0.029.